Advancing a Three-Tier Personality Framework for Posttraumatic Growth. Issue 4 (July 2022) - Weststrate, Nic M.; Jayawickreme, Eranda; Wrzus, Cornelia
Adversity has been assumed to foster positive personality change under certain conditions. In this article, we examine this assumption within the context of the three-tier personality framework integrating traits, characteristic adaptations, and narrative identity to provide a comprehensive understanding of personality growth. We first review findings on how adverse events affect personality on each of these three levels. Second, we summarize knowledge on event-based and person-based predictors of personality change in the face of adversity. Third, we specify affective, behavioral, and cognitive processes that explain personality change across levels of personality. Innovatively, our proposed process model addresses change at all three levels of personality, as well as similarities and differences in processes across the levels. We conclude by discussing unresolved issues, asking critical questions, and posing challenging hypotheses for testing this framework.